DEVELOPMENT OF A WEB-BASED ONLINE QUEUE INFORMATION SYSTEM FOR THE PAGELARAN HEALTH CENTER - Rahima, Gheriya; Muslihudin, Muhamad (Bakti Nusantara Institute, 2025)
The implementation of a web-based queue ticket registration system is an effective solution to improve the efficiency of patient services at the Pagelaran Health Center. Currently, the queue registration process is still done manually by handwriting patient information, which often leads to inefficiencies, long queues, and data errors. This research aims to design a web-based queue information system that simplifies the registration process for both patients and health center staff. The system was developed using the waterfall method with PHP as the programming language and MySQL as the database. The features provided include online patient registration, automatic queue number generation, and queue status display. The results show that the system can reduce waiting times, facilitate real-time access to patient data, and improve service flow. The novelty of this study lies in its development of a simple, adaptable digital solution tailored to health centers still using traditional queue systems, enhancing healthcare access and service quality.